1999
DOI: 10.1016/s0014-5793(99)01156-4
|View full text |Cite
|
Sign up to set email alerts
|

NMR characterization of the NADP(H)‐binding domain of Escherichia coli transhydrogenase: sequential assignment and global fold

Abstract: The soluble NADP(H)-binding domain of Escherichia coli transhydrogenase (186 amino acids, 20.4 kDa, rotational correlation time 14 ns) was characterized using NMR techniques. The global fold is similar to that of a classical dinucleotidebinding fold with six parallel L L-strands in a central sheet surrounded by helices and irregular structures, but is lacking both K KD and K KE. The substrate is bound in an extended conformation at the C-terminal end of the parallel L L-sheet and our data support the notion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…NMR experiments with R. rubrum dIII also indicate that the protein is a monomer (25), although on size-exclusion chromatography it behaves anomalously; the apparent M r value is intermediate between those expected for the monomer and the dimer (13). E. coli dIII is monomeric on size-exclusion chromatography (16), but has an unexpectedly large correlation time in NMR experiments, perhaps indicating some tendency to aggregate (37). Fig.…”
Section: Resultsmentioning
confidence: 88%
“…NMR experiments with R. rubrum dIII also indicate that the protein is a monomer (25), although on size-exclusion chromatography it behaves anomalously; the apparent M r value is intermediate between those expected for the monomer and the dimer (13). E. coli dIII is monomeric on size-exclusion chromatography (16), but has an unexpectedly large correlation time in NMR experiments, perhaps indicating some tendency to aggregate (37). Fig.…”
Section: Resultsmentioning
confidence: 88%
“…However, TH soluble domains have been expressed for biochemical and structural investigations, including human and bovine, Escherichia coli, and R. rubrum domains I and III. [21][22][23][24][25][26][27][28][29][30] Reconstituted mixtures of domain I and domain III catalyze reaction between NAD(H) and NADP(H) in the absence of membrane-bound domain II, and this activity has been studied to characterize the hydride transfer function of TH. [31][32][33][34][35] Regardless of their arrangement in intact TH, the soluble domains must allow the (dihydro)nicotinamide rings of NAD(H) and NADP(H) to come into direct contact.…”
Section: Introductionmentioning
confidence: 99%
“…The structural properties of domain I (dI) and domain III (dIII), from the three sources mentioned previously, have been characterized by expressing them separately. The determination of their structures has been realized by structural predictions [4–6], NMR [6–9] and X‐ray crystallography [10,11]. From these studies, it was found that dI was made of two similar domains (dIa and dIb) each of which comprise a parallel β sheet surrounded by mainly β helices.…”
mentioning
confidence: 99%